(untitled) (KULT_online, 2009)
Kerstin Volland’s doctoral thesis Zeitspieler. Inszenierungen des Temporalen bei Bergson, Deleuze und Lynch (Playing with time: Productions of temporality from Bergson, Deleuze and Lynch) is an ambitious study of the relation between time and film. At the centre of her analysis is an idea of temporality that goes beyond the linear, objective concept of time to encompass the subjective time of thoughts and memories. Volland briefly outlines the discussion surrounding time and media before moving on to a detailed examination of the temporal concepts of Henri Bergson, Gilles Deleuze and David Lynch. Lynch’s films are thereby not seen as illustrating Bergson’s and Deleuze’s theories, but are rather placed on a level with the others for a collective explication of temporal representation in concept and practice.